Collaborative Project Based Learning Pada Mata Pelajaran Geografi: Penerapan Proyek Media Diorama 3D Untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik - Andini, Tri Julia; Suharto, Yusuf (Jayapangus Press, 2024)
The ability to think creatively is a necessary aspect in learning geography to find new ideas or thoughts in solving geosphere problems in the surrounding environment. The low value of students' creative thinking makes geography learning less meaningful, so it is necessary to apply the Collaborative Project Based Learning model through 3D diorama project learning to improve students' low levels of creative thinking. The urgency of this research is to determine the increase in creative thinking skills through the application of the Collaborative Project Based Learning model with 3D diorama projects. This research is a type of participant Classroom Action Research (PTK) using the Kemmis & Mc. Taggart model design which consists of two cycles. The research subjects consisted of 35 students in class X-9 at SMA Negeri 1 Tumpang. Data collection used a creative thinking test consisting of 4 filled-in questions referring to indicators according to Munandar (1999). Data processing was obtained from the results of the spatial thinking test in 2 cycles to determine the improvement at each stage. The research results show that the application of the Collaborative Project Based Learning model with 3D diorama projects has increased significantly from the pre-cycle stage to cycle 2. This is evidenced by the increase in the average value of students' creative thinking abilities from pre-cycle which has a value of 59.94 to cycle 1 it was 71.20 or experienced a percentage increase of 19% and cycle 1 with a value of 71.20 to cycle 2 obtained an average value of 82.29 or experienced a percentage increase of 16%. The application of the CPBL model through the 3D diorama project is able to provide space for student collaboration to find innovations or new ideas to solve geosphere problems through making this project.